Devaluation expectations and speculative attacks on the currency - Alpo Willman (Bank of Finland, 1988)
In this paper balance-of-payments crises are studied in a framework in which investors do not know the threshol~ level of foreign reserves, the attainment of which implies that the central bank abandons its fixed exchange target. Investors are alternatively risk neutral or risk averters. It is shown that, depending on whether the threshold level is stochastic or fixed but unknown to investors, currency speculation reveals itself as, respectively, a speculative outflow distributed over a longer time period or a sudden speculative attack on the currency.
URN:NBN:fi:bof-201807301738
Keywords: 330